THE STUDENT ENGLISH CLUB OF SANTO PETRUS SENIOR HIGH SCHOOL IN PONTIANAK - Gunawan, .; Supardi, Iwan; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Â Abstract: The aim of this research is to explore an extracurricular activity for English subject inÂ a school which is called with English Club. Besides, the writer also wanted to know the contribution of the English club on the students' English learning. Therefore, the writer used a descriptive method in this research. After conducting the research, the writer found a lot of information about the English club. In the English club, it is not a compulsory for the students to join the English club. In other word, the students are free whether they want to join the English club or not. Then, in the English club, the students do any activities that can promote their English learning. And, the average scores of the students who join the English club is higher than the students who do not join the English club. Â Keywords: English Club, Trainer, Students Abstrak: Tujuan dari penelitian ini adalah untuk mencari tau sebuah kegiatan ekstrakurrikuler untuk mata pelajaran bahasa inggris di sekolah yang di sebut dengan English club. Selain itu, penulis juga ingin mengetahui kontribusi dari English club tersebut pada pembelajaran bahasa Inggris siswa. Oleh karna itu, penulis menggunakan metode deskriptif di dalam penelitian ini. Setelah menyelenggarakan penelitian nya. penulis menemukan banyak informasi tentang English club. Di dalam English club, bukan merupakan kewajiban bagi siswa untuk bergabung dengan nya. Dengan kata lain, para siswa bebas untuk bergabung atau tidak. Kemudian, di dalam English club, para siswa melakukan berbagai kegiatan yang bisa mempromosikan pembelajaran bahasa Inggris mereka. Dan, nilai rata-rata siswa yang bergabung dengan English club lebih tinggi daripada siswa yang tidak bergabung di dalam English club tersebut. Kata Kunci: English Club, Pelatih, Siswa